The Twelfth-Century Renaissance : A Reader - Novikoff, Alex J (Book collections on Project MUSE., 2017)
"The twelfth century was an age of institutional expansion, intellectual creativity, and high adventure, characterized by patron-monarchs like King Henry II and Eleanor of Aquitaine, poets like Marie de France and Chretien de Troyes, lovers and intellectuals like Abelard and Heloise, and religious thinkers like Bernard of Clairvaux and Hildegard of Bingen. In his thoughtful introduction to this important new collection of primary source documents, Alex J. Novikoff explores the historiographical debate surrounding the application of the term "Renaissance" to the twelfth century. Classic works as well as a number of lesser known readings, some of which are translated here for the first time, are included. The overwhelming majority of the sources date from 1075 to 1225, with a focus on Northwestern Europe."--